Potential cardioprotective effect of chronic, moderate consumption of reduced-alcohol wine in a rat model of pulmonary hypertension - Diaba-Nuhoho, Patrick (Division of Anatomical Pathology, 2019)
Background: Pulmonary arterial hypertension (PAH) is a severe disease which leads to right ventricular (RV) dysfunction and possibly death. The pathophysiological process of PAH remains unclear but oxidative stress is thought to contribute to arterial and ventricular dysfunction. Red wine has powerful antioxidant properties and is cardioprotective. However, side effects of alcohol may limit the use of wine as a therapeutic agent. The aim of this study was to test whether reduced-alcohol red wine (RARW) or regular red wine (RW) consumption would limit monocrotaline (MCT)-induced PAH in rats. Methods: Long Evans male rats (150-175g) were randomly assigned into 6 groups: (1) Control: no subcutaneous injection of MCT; (2) MCT; (3) RARW; (4) MCT-Treated with RARW: 5.5% alcohol red wine (5) RW and (6) MCT-Treated with RW: 15% alcohol red wine. The wines were diluted with water (1:7), to supply an equivalent of 2-3 glasses daily consumed in humans ad libitum for 7 days before MCT treatment and for 28 days after MCT treatment with 80mg/kg. The stability of the wine was determined for 4 weeks by analysing ORAC values, total phenolic concentration, anthocyanin and catechin concentrations. Prior to randomisation, and at day 28, echocardiography (VEVO 2100, Visualsonics Inc.) was performed to evaluate pulmonary artery acceleration time (PAAT), an accurate estimate of pulmonary artery pressure, PAAT/Ejection fraction and RV thickness as a marker of RV hypertrophy. Oxidative stress was evaluated by measuring lipid peroxidation markers (conjugated dienes (CD), thiobarbituric acid reactive substances (TBARS)) and antioxidant measures of oxygen radical absorbance capacity (ORAC), superoxide dismutase (SOD) and catalase (CAT) activities in blood plasma were analysed. Results: Baseline echocardiography showed similar cardiac function amongst all groups. MCT injection induced right ventricular hypertrophy compared to controls (1.22 ± 0.01 mm and 0.52 ± 0.04 mm; p< 0.0001). A decrease in PAAT was observed in the MCT group compared to controls (13.95 ± 0.95 vs 23.43 ± 1.64 ms, p< 0.001). However, MCT treatment with RARW ameliorated the trend in the MCT group (18.93 ± 1.80 vs 13.95 ± 0.95 ms, p=0.02). Similarly, PAAT/Ejection fraction in the MCT group was reduced compared to the control group (0.18 ± 0.02 ms and 0.32 ± 0.18 ms; p< 0.001). Chronic moderate treatment with RARW in PAH animals improved hypertrophy and PAAT/Ejection fraction (0.85 ± 0.07 mm; P< 0.001and 0.25 ± 0.30 ms, respectively; p=0.02 versus the MCT group). Oxidative stress markers showed an increase in CD amongst animals with MCT compared to controls (671.60 ± 42.53 nmol/L and 453.10 ± 34.76 nmol/L; p=0.004). Chronic moderate treatment with RARW reduced lipid peroxidation (CD: 471.60 ± 27.45 nmol/L; p=0.004 versus the MCT group). Plasma TBARS, ORAC, SOD and CAT were not significantly affected by the condition or the treatment. The RARW had a consistently higher antioxidant status than the RW for the duration of the study. The mean concentration of RARW to the RW after 4 weeks in the total phenol was (291.90 ± 10.42 vs 235.80 ± 9.22 mg/L, p=0.006), that of the anthocyanins was (190.00 ± 3.53 vs 172.20 ± 5.13 mg/L M-3-G, p=0.0008), that of catechin was (12.06 ± 0.31 vs 10.26 ± 0.19 mg/L, p=0.157), and that of ORAC was (32.55 ± 2.75 vs 26.55 ± 2.37 nmol/L trolox equivalents, p=0.983). Conclusion: This study suggests that a moderate and chronic treatment with RARW but not RW attenuates MCT-induced PAH in rats, an effect which may be mediated, at least in part, by reduction of lipid peroxidation. The use of RARW could be tested in a randomised controlled trial and may be more beneficial than RW. This simple, inexpensive treatment might represent a new therapeutic option for PAH